ANALISIS PELAKSANAAN PERATURAN WALIKOTA NO.40 TH. 2014 TENTANG PEDOMAN PROGRAM FASILITASI PEMBERDAYAAN MASYARAKAT DI KECAMATAN MOJOROTO KOTA KEDIRI - Hanum, Fauziah (Universitas Kadiri, 2019)
Abstract Comunnity empowerment program (PRODAMAS) is an activity of the Kediri city government to improve community welfare. The target of the program is the community in the neighborhood in Kediri City, namely strengthening institutions, training, skills and social activities to increase the response to the awareness of participating in planning is a difficulty in itself. When building basic environmental facilities and infrastructure that should involve community members, the opposite often occurs, namely reluctance from residents because they feel that these activities only benefit certain groups. The result is that the implementation of basic environmental development is not satisfactory because it is not in accordance with the wishes of the resident. The supervision that is expected to arise by itself is ineffective because the making of development planning and the implementation of development activities that should be carried out by the community is still far from being expected because of the assumption that the task of supervising is a committee or government that has been formed so that the community tends not to carry out supervision. On the other hand, there is an attitude of society that is less supportive. For this reason, researchers are interested in analyzing the implementation of Kediri Mayor Regulation No. 40/2014 in Mojoroto District, Kediri City. The analysis used in this research is descriptive analysis. The results of the research and the focus of the research are that the planning stages have been carried out in accordance with the guidelines for implementing the implementation stages. Keywords: Prodamas; Implementation; Empowerment Abstrak Program Pemberdayaan Masyarakat (PRODAMAS) adalah kegiatan Pemerintah Kota Kediri untuk meningkatkan kesejahteraan masyarakat. Sasaran program adalah masyarakat di wilayah Rukun Tetangga di Kota Kediri, yakni penguatan kelembagaan, pelatihan, keterampilan dan kegiatan sosial untuk menambah respon akan kesadaran berpartisipasi dalam perencanaan adalah sebuah kesulitan tersendiri. Pada waktu melakukan pembangunan sarana dan prasarana dasar lingkungan yang seharusnya melibatkan warga masyarakat sering terjadi hal sebaliknya yaitu timbul rasa enggan dari warga karena mereka merasa kegiatan itu hanya memberikan manfaat bagi kelompok tertentu. Hasilnya pelaksanaan pembangunan dasar lingkungan kurang memuaskan disebabkan tidak sesuai dengan keinginan warga. Pengawasan yang di harapkan timbul dengan sendirinya tidak efektif karena pembuatan perencanaan pembangunan serta kegiatan pelaksanaan pembangunan yang seharusnya dilakukan oleh masyarakat sedikitpun tampaknya masih jauh dari harapan karena adanya anggapan bahwa yang bertugas melakukan pengawasan adalah pihak panitia atau pemerintah yang telah dibentuk sehingga cenderung masyarakat tidak melakukan pengawasan. Disisi lain ada sikap masyarakat yang kurang mendukung. Dengan alasan itulah peneliti tertarik untuk menganalisis pelaksanaan peraturan Walikota Kediri No 40 Tahun 2014 di Kecamatan Mojoroto Kota Kediri. Analisis yang digunakan dalam penelitian ni adalah analisis deskriptif. Hasil penelitian dan fokus penelitian adalah tahapan perencanaan telah dilaksanakan sesuai dengan pedoman pelaksanaan tahapan pelaksana. Kata Kunci: Prodamas; Pelaksanaan; Pemberdayaan